Comparison of Characteristics and Antibacterial Activity of Mandai Cempedak Vinegar with Variations in Fermentation Methods - Utami, Indah Woro; Sapri, Sapri; Meray, Nishia Waya; Canrika, Rezia Elok (Borneo Journal of Pharmacy, 2025)
Mandai, a traditional fermented food product from East Kalimantan, is derived from the edible mesocarp of the cempedak (Artocarpus champeden) fruit. This ancestral fermentation technique, passed down through generations, is known to produce lactic acid bacteria (LAB) with potential probiotic properties. This study aimed to characterize LAB isolated from mandai vinegar and evaluate their antibacterial activity under two distinct fermentation conditions: a defined starter culture of Lactobacillus casei strain Shirota and spontaneous fermentation in a 10% NaCl solution. The latter, referred to as salt fermentation, yielded three bacterial colonies, while the starter culture method produced four. All isolates from both methods shared similar morphological characteristics, including a rod shape, white coloration, entire margins, and convex surfaces. Further analysis confirmed they were Gram-positive, catalase-negative, and indole-negative, with the ability to ferment various carbohydrates. While all LAB isolates demonstrated generally low antibacterial activity against Escherichia coli ATCC 25922, isolate CML 1 exhibited the highest antibacterial potential. These findings highlight the potential of mandai vinegar as a source of functional LAB, warranting further investigation into its applications as a functional food ingredient.